Perancangan Aplikasi E-Learning Berbasis Web Dengan Metode Waterfall Di PT. Wellmagic Media Digital - Fauzan, Ahmad; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
E-learning has now become an innovative alternative solution in the field of education to enhance the flexibility and efficiency of teaching and learning processes, especially in the digital era. This study aims to design an e-learning platform using the Waterfall method at PT. Wellmagic Media Digital. The Waterfall method was chosen for its advantages in providing a clear and organized structure, particularly for projects with well-defined requirements that rarely change. Each stage of the development process, such as requirement analysis, design, implementation, testing, and deployment, is carried out sequentially with comprehensive documentation at each step. This approach ensures that development progresses systematically and aligns with the initial specifications, minimizing the risk of misalignment with user needs. This e-learning application is designed to facilitate the management of digital materials, automated assessments, student progress monitoring, and digital attendance recording. Trials conducted indicate that this application can enhance student engagement and learning experiences while simplifying online teaching management for educators. With these results, the application is expected to become an innovative solution for improving the quality of technology-based education. This study contributes significantly to the advancement of e-learning that is responsive to user needs in the digital era.